2009
DOI: 10.1002/rcm.3977
|View full text |Cite|
|
Sign up to set email alerts
|

Revised δ34S reference values for IAEA sulfur isotope reference materials S‐2 and S‐3

Abstract: Revised delta(34)S reference values with associated expanded uncertainties (95% confidence interval (C.I.)) are presented for the sulfur isotope reference materials IAEA-S-2 (22.62 +/- 0.16 per thousand) and IAEA-S-3 (-32.49 +/- 0.16 per thousand). These revised values are determined using two relative-difference measurement techniques, gas source isotope ratio mass spectrometry (GIRMS) and double-spike multi-collector thermal ionization mass spectrometry (MC-TIMS). Gas analyses have traditionally been conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 56 publications
(88 reference statements)
0
54
1
Order By: Relevance
“…34 S/ 32 S ratios were measured by combustion-isotope ratio monitoring-mass spectrometry (C-irm-MS) using a Thermo Finnigan MAT 253 mass spectrometer coupled to an elemental analyzer (Thermo Flash 2000) via a split interface (Thermo Finnigan Conflo IV). Measured isotope ratios were calibrated with in-house and international reference materials (Mann et al, 2009) and reported in the δ-notation relative to the V-CDT (Vienna Cañon Diablo Troilite) standard.…”
Section: Methodsmentioning
confidence: 99%
“…34 S/ 32 S ratios were measured by combustion-isotope ratio monitoring-mass spectrometry (C-irm-MS) using a Thermo Finnigan MAT 253 mass spectrometer coupled to an elemental analyzer (Thermo Flash 2000) via a split interface (Thermo Finnigan Conflo IV). Measured isotope ratios were calibrated with in-house and international reference materials (Mann et al, 2009) and reported in the δ-notation relative to the V-CDT (Vienna Cañon Diablo Troilite) standard.…”
Section: Methodsmentioning
confidence: 99%
“…grade V 2 O 5 , and combusted in a Thermo Scientific FLASH 2000 elemental analyser coupled to a Thermo Finnigan 253 gas mass spectrometer via a Thermo Scientific ConFlo IV split interface. Silver sulphide isotope reference materials (IAEA-S-1, IAEA-S-2 and IAEA-S-3) were used to link the mass spectrometric results towards the V-CDT scale [38]. Isotope measurements are given in the conventional δ notation, and replicate measurements agreed within better than ±0.3 ‰.…”
Section: Methodsmentioning
confidence: 99%
“…Stable sulphur isotope measurements were carried out with a Thermo Finnigan MAT 253 gas mass spectrometer that was connected to via a Thermo Electron ConFlo IV split interface to a Thermo Scientific Flash 2000 elemen-tal analyzer. Silver sulphide isotope reference materials (IAEA-S-1, IAEA-S-2 and IAEA-S-3) were used to link the mass spectrometric results ( 34 S/ 32 S) to the V-CDT scale (MANN et al, 2009). Replicate measurements agreed within better than ±0.3‰.…”
Section: Stable Isotopes Of Boronmentioning
confidence: 99%